Price trends over the product life cycle and the optimal inflation target - Klaus Adam; Henning Weber (Deutsche Bundesbank, 2019)
We document a new stylized fact for the life-cycle behavior of consumer prices: relative to a narrowly defined set of competing products, the price of individual products tends to fall over the product lifetime. This holds true for more than 90% of the expenditure items underlying the U.K. consumer price index and has important normative implications. Constructing a sticky price model featuring a product life cycle and rich amounts of heterogeneity, we explain how the optimal in ation target can be estimated from the observed trends in relative prices. The optimal inflation target for the U.K. is found to range between 2.6% and 3.2% and to have steadily increased over the period 1996 to 2016. We show how changes in relative price trends contributed to this development.
Keywords: E31; 330; Optimal Inflation Rate; Product Life Cycle; U.K. Micro Price Data